Analisis Pendekatan Sosiologis Pendidikan Karakter Dalam Pembelajaran Di Madrasah Alyah Negeri 1 Kota Baubau - Norliani Norliani; Wistina Seneru; Fitrisiswanty Fitrisiswanty; Antonius Rino Vanchapo; Nur Kholis; Hamirul Hamirul (Departement of Mathematics Education, 2023)
This study aims to find out about the ongoing process of character education carried out by Madrasah Aliyah Negeri 1 Baubau City, as well as the impact of this character education on changes in student behavior. This study uses a descriptive research method with a qualitative approach. The data analysis technique uses the data analysis model of Miles and Huberman with the processes of data reduction, data validation and data inference. The result of his research is that character education carried out by Madrasah Aliyah Negeri 1 Baubau City is going well and students can understand and apply it in everyday life because of the habituation carried out at the Madrasah. The application of character education through a sociological approach by forming study groups to discuss and provide material with the lecture method carried out in the teaching and learning process as well as habits carried out by the Madrasah Aliyah Negeri 1 Baubau City. Character education carried out by Madrasah Aliyah Negeri 1 Baubau City has had a good impact on student behavior. Judging from the way students carry out the learning process in an orderly manner, sit and tell stories with friends, teachers, and security during recess or empty class hours, as well as students who always try to be on time when attending the midday prayers in congregation at school. Based on the sociological point of view of character education carried out by the Baubau City Aliyah 1 Public Elementary School, it follows the values prevailing in the surrounding community. Based on the results of this study, it can be concluded that character education carried out by Madrasah Aliyah Negeri 1 Baubau City is going very well and has a good impact on changing student behavior.